The role of teachers in the prevention and management of childhood obesity among school-aged children in Ghana: a cross-sectional study - Kayitesi, Chantal; Tagoe, Nadia; Acheampong, Princess Ruhama (Frontiers in Public Health, 2025)
BackgroundSchool-based interventions have been widely used in the prevention and control of childhood obesity. Teachers, as pivotal figures in child development, are strategically situated to aid in this process. Nonetheless, there is limited evidence regarding their role, awareness, and contribution to childhood obesity in Ghana. This study evaluated the role of teachers in the prevention and management of childhood obesity in Ghana.Materials and methodsThis quantitative, cross-sectional study included 74 teachers selected through convenience sampling from public schools in the Oforikrom Municipality of Kumasi, the capital of Ghana’s Ashanti Region. Data were gathered using a structured pre-tested questionnaire and analyzed using the R programming software. Binary logistic regression was performed to identify the factors associated with teacher’s participation in childhood obesity prevention programs.ResultsThe study revealed that 46% of teachers were familiar with childhood obesity with only 33.8% of teachers familiar with its causes. Significant institutional hurdles included resource restrictions (46%), insufficient training (24.3%), and time constraints (12.2%). Chi-square analysis revealed that teachers’ participation in childhood obesity prevention was significantly associated with socioeconomic conditions (p = 0.016), challenges faced (p = 0.022), perception of physical activity (p = 0.012), physical education practices (p = 0.006), outdoor play promotion (p = 0.026), health screenings (p = 0.002), healthy eating education (p = 0.002), and counseling practices (p < 0.001). However, the multivariable logistic regression analysis revealed no statistically significant determinants of teachers’ participation.ConclusionThe results highlight the necessity for specific measures, including professional development initiatives, institutional policy modifications, and resource distribution, to improve teachers’ ability to combat childhood obesity. Policymakers ought to incorporate comprehensive school health initiatives into the curriculum, prioritizing physical exercise and nutritious food.